Bioinspired magnetic nanocomplexes amplifying STING activation of tumor-associated macrophages to potentiate cancer immunotherapy. (April 2022) - Li, Tianliang; Song, Rundi; Sun, Fang; Saeed, Madiha; Guo, Xiaozhen; Ye, Jiayi; Chen, Fangmin; Hou, Bo; Zhu, Qiurong; Wang, Yingjie; Xie, Cen; Tang, Lei; et al.
Highlights: Magnetic nanocomplexes boosted cancer immunotherapy by relieving immunosuppressive tumor microenvironment and activating CTLs. Magnetic nanocomplexes repolarized TAMs into M1 phynotypes, and activated the STING pathway in the M1Ф TAMs for eliciting the immune cascade. Magnetic nanocomplexes recruited the tumor-infiltrating DCs for priming CTLs, inhibited tumor growth and metastasis by combining with αPDL1. Graphical Abstract: ga1 Bioinspired magnetic nanocomplexes were engineered to boost STING-based antitumor immune cascade via relieving the immunosuppressive tumor microenvironment (ITM) and activating the tumor-specific cytotoxic T lymphocytes (CTLs). The nanocomplexes repolarized tumor-associated macrophages (TAMs) into M1 phynotype, activated the STING pathway in M1 TAMs for recruiting the conventional type Ⅰ dendritic cells and CTL priming, and eventually regressed tumor growth and suppressed metastasis of the tumor cells. Abstract: Insufficient tumor-infiltration of the cytotoxic T lymphocytes (CTLs) and immunosuppressive tumor microenvironment (ITM) severely hinder T cell-based cancer immunotherapy. In this study, we developed bioinspired magnetic nanocomplexes (m-PUNCs) to boost antitumor immunogenicity through amplifying stimulator of interferon genes (STING)-regulated immune cascade of tumor-associated macrophages (TAMs). m-PUNCs were engineered by integrating ultrasmall iron oxide nanoparticles (UIONPs), tumor acidity-ionizable of poly(ethylene glycol)- block -poly(2-(hexamethyleneimino)) ethyl methacrylate (PHMA) diblock copolymer, and red blood cell membrane into a single nanoplatform. The resultant m-PUNCs specifically accumulated at the tumor site via passive targeting effect, which were subsequently phagocytized with TAMs. The UIONPs moiety efficiently relieved the ITM by repolarizing TAMs into M1-phenotype, while PHMA activated the STING pathway and stimulated type-I interferon (e.g., IFN-β) secretion in TAMs. Consequently, IFN-β attracted the conventional type I dendritic cells for priming the tumor-specific CTLs. In combination with immune checkpoint blockade therapy with the antibody against programmed death ligand 1, m-PUNCs remarkably inhibited tumor growth and prolonged the survival of both melanoma and breast tumor-bearing mouse model. This study demonstrated the immune cascade of magnetic nanocomplexes-mediated TAM repolarization and subsequent STING activation, which might provide novel insights for potentiating cancer immunotherapy.